Parallel science and engineering applications : the Charm++ approach - Kale, Laxmikant V.; Bhatele, Abhinav (Series in computational physics., 2013)
Developed in the context of science and engineering applications, with each abstraction motivated by and further honed by specific application needs, Charm++ is a production-quality system that runs on almost all parallel computers available. Parallel Science and Engineering Applications: The Charm++ Approach surveys a diverse and scalable collection of science and engineering applications, most of which are used regularly on supercomputers by scientists to further their research. After a brief introduction to Charm++, the book presents several parallel CSE codes written in the.